Strategi Marketing Politik Anies Baswedan Pada Pilpres 2024 Melalui “Desak Anies” (Studi Kasus di Jakarta) - Ardiansyah, Atih; Priyanto, Arkaan Ade (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2025)
This research attempts to elaborate the political marketing strategy carried out by Anies Baswedan with the “Desak Anies” program in the 2024 Presidential Election conducted in Jakarta, using the 3P concept of push, pass and pull marketing. Through interviews, observations and documentation studies, this research shows that the Desak Anies Team uses a push marketing strategy by building direct relationships between candidates and voters through two-way communication. The pass marketing strategy is used by targeting the involvement of youth organizations as influencers. Meanwhile, the pull marketing strategy was used by the Desak Anies Team by spreading the content of the event and Anies Baswedan's figure through social media. The Desak Anies Team combined the three political marketing strategies in order to market the event as well as Anies Baswedan's figure as an Indonesian presidential candidate to potential voters, both in Jakarta directly and to other regions through social media. This research contributes to the understanding of political marketing strategies in the context of election campaigns in Indonesia.Keywords: Political Marketing Strategy; Campaign; Desak Anies Jakarta